LEGAL RESPONSIBILITY FOR THE USE OF ARTIFICIAL INTELLIGENCE IN MEDICAL PRACTICE - Ardiyanti, Novita; Azmi, Rahma Nur Kamilatul; Ramadhan, Noval; Jamaludin, Ahmad (DE'RECHTSSTAAT, 2024)
The use of Artificial Intelligence in the medical world is a form of development and implementation of technology in the medical world. Indonesia is a country of law where everything that happens in Indonesia must be based and rely on the law. This research uses a normative juridical method using a conceptual approach by examining laws, articles, and also secondary and primary data sources related to the title to be analyzed. After reviewing it, the use of AI in the world of medicine really helps make things easier for health and medical workers. Meanwhile, legal responsibility for the use of AI in the world of medicine itself is borne by the creators of artificial intelligence and AI users, or in this case, the medical personnel themselves.